2014
DOI: 10.1210/en.2013-1561
|View full text |Cite
|
Sign up to set email alerts
|

Role of Androgen and Estrogen Receptors for the Action of Dehydroepiandrosterone (DHEA)

Abstract: Dehydroepiandrosterone (DHEA) is an abundant steroid hormone, and its mechanism of action is yet to be determined. The aim of this study was to elucidate the importance of androgen receptors (ARs) and estrogen receptors (ERs) for DHEA function. Orchidectomized C57BL/6 mice were treated with DHEA, DHT, 17β-estradiol-3-benzoate (E2), or vehicle. Orchidectomized AR-deficient (ARKO) mice and wild-type (WT) littermates were treated with DHEA or vehicle for 2.5 weeks. At termination, bone mineral density (BMD) was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Accordingly, after menopause all estrogens are made locally from DHEA by the mechanisms of intracrinology (73). DHEA activates ERβ to nearly the same extent as E2 and it activates ERα to a lesser extent (38,66). The current data showed that administration of BSNXD increased the serum concentration of DHEA but not that of E2.…”
Section: Discussionmentioning
confidence: 42%
“…Accordingly, after menopause all estrogens are made locally from DHEA by the mechanisms of intracrinology (73). DHEA activates ERβ to nearly the same extent as E2 and it activates ERα to a lesser extent (38,66). The current data showed that administration of BSNXD increased the serum concentration of DHEA but not that of E2.…”
Section: Discussionmentioning
confidence: 42%
“…It has been reported that ER and AR are involved in the action of DHEA ( 37 , 38 ). Then, experiments were conducted to determine the expression of ER and AR during B. abortus infection and their modulation by cortisol and DHEA.…”
Section: Resultsmentioning
confidence: 99%
“…Although the ability of AR and ER to mediate DHEA signaling was described in different cell types ( 37 , 38 ); it has been reported that DHEA seems to act on osteoblast through the MAPK signaling pathway involving ERK1/2 in a way that is mainly modulated by ERβ instead of AR. In concordance, DHEA could reverse the inhibitory effect of B. abortus infection on ERβ expression in osteoblast (Figure 7 B).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, DHEA mediated this effect through ER receptor as evidenced when infections and the treatment with supernatants from B. abortus -infected monocytes were performed in the presence of fulvestrant. The ability of DHEA and its metabolites to signal through androgen receptor (AR) and ER has been previously described (43, 44). However, since the addition of ER antagonist, fulvestrant, completely avoids the effect of DHEA on RANKL expression, we could affirm that the main signaling of DHEA during B. abortus infection in sinoviocytes is via ER.…”
Section: Discussionmentioning
confidence: 99%